The role of educational innovation in strengthening religious moderation and social harmony - Sholeh Utomo; Imam Nururi; Asep Yudianto (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The cultivation of religious moderation remains a crucial issue in Indonesia due to the persistent occurrence of religious conflicts across the country. Previous studies have highlighted the importance of educational institutions in promoting tolerance and inclusivity, yet few have focused on the role of Islamic boarding schools (pesantren). Therefore, this study aims to explore the strategies and innovations implemented by Mathlaul Huda Islamic Boarding School in fostering religious moderation among its students. Methods: This study employed a qualitative approach through interviews, observations, and document analysis. The analysis was guided by Albert Bandura’s Social Learning Theory, which emphasizes that individuals learn through observation, imitation, and modeling. This theory served as the theoretical foundation to understand how moderate behaviors are transmitted through the daily practices of kyai (religious leaders), ustadz (teachers), and other influential figures within the boarding school community. Findings: The results revealed that innovation plays a vital role in the successful integration of religious moderation education in a traditional Islamic boarding school environment. Mathlaul Huda Islamic Boarding School has effectively cultivated moderate and tolerant students by implementing a moderation-based curriculum, inclusive teaching strategies, and community engagement programs. The school’s initiatives have contributed positively to building an inclusive and harmonious society that values diversity, tolerance, and respect. Conclusion: Mathlaul Huda Islamic Boarding School has successfully implemented innovative strategies to promote religious moderation and tolerance among students, providing a model for other Islamic boarding schools in Indonesia. Novelty/Originality of this article: This study presents a unique exploration of how traditional Islamic boarding schools can integrate modern approaches and social learning theory to promote religious moderation, offering new insights into the practical application of innovation in religious education settings.